Mechanochemistry: A Green Approach in the Preparation of Pharmaceutical Cocrystals - Mizraín Solares-Briones; Guadalupe Coyote-Dotor; José C. Páez-Franco; Miriam R. Zermeño-Ortega; Carmen Myriam de la O Contreras; Daniel Canseco-González; Alcives Avila-Sorrosa; David Morales-Morales; Juan M. Germán-Acacio (MDPI AG, 2021)
Mechanochemistry is considered an alternative attractive greener approach to prepare diverse molecular compounds and has become an important synthetic tool in different fields (e.g., physics, chemistry, and material science) since is considered an ecofriendly procedure that can be carried out under solvent free conditions or in the presence of minimal quantities of solvent (catalytic amounts). Being able to substitute, in many cases, classical solution reactions often requiring significant amounts of solvents. These sustainable methods have had an enormous impact on a great variety of chemistry fields, including catalysis, organic synthesis, metal complexes formation, preparation of multicomponent pharmaceutical solid forms, etc. In this sense, we are interested in highlighting the advantages of mechanochemical methods on the obtaining of pharmaceutical cocrystals. Hence, in this review, we describe and discuss the relevance of mechanochemical procedures in the formation of multicomponent solid forms focusing on pharmaceutical cocrystals. Additionally, at the end of this paper, we collect a chronological survey of the most representative scientific papers reporting the mechanochemical synthesis of cocrystals.